PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE INSIDE OUTSIDE CIRCLE TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SEMESTER GENAP SMA NEGERI 3 METRO TAHUN PELAJARAN 2018/2019 - Adelia Putri Rahayu; Ningrum Ningrum; Tiara Anggia Dewi (Universitas Muhammadiyah Metro, 2021)
The Cooperative Learning model Inside Outside Circle is a learning strategy that allows students to exchange information at the same time and so that students can think critically and improve communication skills towards their learning outcomes, by applying the inside outside circle model in the classroom when the learning process will certainly make students produce meaningful knowledge.As for the problems in the research conducted by researchers,